Endosomal Accumulation of Toll-Like Receptor 4 Causes Constitutive Secretion of Cytokines and Activation of Signal Transducers and Activators of Transcription in Niemann–Pick Disease Type C (NPC) Fibroblasts: A Potential Basis for Glial Cell Activation in the NPC Brain - Suzuki, Michitaka (J Neurosci, 2007)
Niemann–Pick disease type C (NPC) is an inherited lipid storage disorder caused by mutations in NPC1 or NPC2 genes. Loss of function of either protein results in the endosomal accumulation of cholesterol and other lipids, progressive neurodegeneration, and robust glial cell activation. Here, we report that cultured human NPC fibroblasts secrete interferon-β, interleukin-6 (IL-6), and IL-8, and contain increased levels of signal transducers and activators of transcription (STATs). These cells also contained increased levels of Toll-like receptor 4 (TLR4) that accumulated in cholesterol-enriched endosomes/lysosomes, and small interfering RNA knockdown of this receptor reduced cytokine secretion. In the NPC1(−/−) mouse brain, glial cells expressed TLR4 and IL-6, whereas both glial and neuronal cells expressed STATs. Genetic deletion of TLR4 in NPC1(−/−) mice reduced IL-6 secretion by cultured fibroblasts but failed to alter STAT levels or glial cell activation in the brain. In contrast, genetic deletion of IL-6 normalized STAT levels and suppressed glial cell activation. These findings indicate that constitutive cytokine secretion leads to activation of STATs in NPC fibroblasts and that this secretion is partly caused by an endosomal accumulation of TLR4. These results also suggest that similar signaling events may underlie glial cell activation in the NPC1(−/−) mouse brain.